The relationship between smartphone addiction and depression among health sciences students in the National University of Malaysia - Nurul Farhana Jufri; Aslam Nornah; Ismail Salma; Lujain Akram; Pelden Wangchuk; Restu Wahyu; Wibawati; Zainab Alsaihaty; Siti Fathiah Masre; Nur Zakiah; Mohd Saat (Penerbit Universiti Kebangsaan Malaysia, 2022)
The COVID-19 pandemic has seen the increased of online activities as there were restriction on face-to-face activities to curb the disease. One of the popular gadgets used is via smartphone. Smartphones are essential nowadays as many essential tasks been assisted by this device. However, the overuse of smartphones is worrying as it could disturb users’ daily lives and mental state such as anxiety and depression. Thus, this study aims to investigate the relationship between smartphone addiction and depression among Health Science students of Universiti Kebangsaan Malaysia. This is a cross-sectional study by using convenience sampling. A questionnaire was distributed to undergraduate and postgraduate students of Faculty Health Science in Universiti Kebangsaan Malaysia. Participants were required to fill in online questionnaires which comprised three sections: sociodemographic data, Smartphone Addiction Scale - Short Version (SAS-SV), and Beck Depression Inventory-II (BDI-II). A total of 79 respondents were obtained. The mean score for SAS was 34.8 ± 10.068 and the mean score for BDI was 11.92 ± 10.19. There were no significant differences between smartphone addiction and depression according to the gender and education level found in this study. A positive and moderate correlation was found between smartphone addiction and depression (r=0.497, p<0.001). The present study showed that almost 65% of health science students in Universiti Kebangsaan Malaysia showed slightly addicted to smartphones and almost 50% showed to have depression symptoms from mild to severe levels during pancemic. Thus, awareness about the effects should be integrated in their activities to prevent more severe effects.